The centenary of José Martí in Repertorio Americano - Núñez Rodríguez, Mauricio (2021)
This essay analyzes the role of Repertorio Americano during its 39 years of life along with other leading Latin American journals. The uniqueness of Repertorio Americano stands out for being a magazine in the hands of a single person: Joaquín García Monge. The importance of José Martí in Costa Rica is also analyzed, as well as the tribute of Repertorio Americano in the 50 years since his death, and the presence of other great Latin American intellectuals.